Single Mothers and Child Support in Extended-Family Households: Insights from Six Latin American Countries - Guarin, Angela; Mesiaislehto, Merita; Hakovirta, Mia; Costanzo, Molly (OXFORD UNIV PRESS, 2026)
Extended-family households are common among single mothers. Using Luxembourg Income Study data from waves 2014-2019, we study child support receipt among single mothers living in extended-family households in Chile, Guatemala, Panama, Paraguay, Peru, and Uruguay. We have three aims: to present the prevalence and characteristics of single mothers living with relatives, compare the level of child support received by extended-family and other single-mother households, and examine whether living in an extended-family household predicts child support receipt. We find the characteristics of mothers in extended-family households vary by country. Overall, these mothers are younger, have lower levels of education, are less likely to be employed, and are, in half of the countries, less likely to receive child support. This has important gender implications, as cultural norms around caregiving often place the financial burden on women, while fathers may reduce their financial contributions when mothers live with other relatives.